2020
DOI: 10.1002/bmc.4835
|View full text |Cite
|
Sign up to set email alerts
|

A validated surrogate analyte UPLC–MS/MS assay for quantitation of TUDCA, TCDCA, UDCA and CDCA in rat plasma: Application in a pharmacokinetic study of cultured bear bile powder

Abstract: Bear bile is a valuable medicinal material used in traditional Chinese medicine for over 2000 years. However, developing a substitute has become necessary because of protection measures for this endangered species. The ingredients of in vitro cultured bear bile powder (CBBP) include tauroursodeoxycholic acid (TUDCA), taurochenodeoxycholic acid (TCDCA), ursodeoxycholic acid (UDCA) and chenodeoxycholic acid (CDCA, and it has pharmacological properties that are similar to those of natural bear bile powder (NBBP).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…[2][3][4][5] Intestinal epithelial homeostasis relies on the balance between cell proliferation and cell death. 10 Cell proliferation is essential for driving intestinal epithelial renewal and injury repair. Cell apoptosis, a programmed cell death process executed by caspase family proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Intestinal epithelial homeostasis relies on the balance between cell proliferation and cell death. 10 Cell proliferation is essential for driving intestinal epithelial renewal and injury repair. Cell apoptosis, a programmed cell death process executed by caspase family proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been validated that TCDCA is an effective FXR endogenous regulator and considered a functional molecule applicable for clinical auxiliary treatment. 9,10 Recent studies have demonstrated that TCDCA can not only suppress the proliferation and invasion of gastric cancer cells but also increase the apoptosis of cancer cells, exerting inhibitory effects on cancer cell proliferation. 11 Additionally, TCDCA can inhibit the expression of the FXR in the small intestine and thus regulate the metabolism of lipids in humans and mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of chenodeoxycholic acid have demonstrated that TCDCA is anti‐inflammatory, antipyretic, analgesic, and bacteriostatic and can regulate immune cells (Brass et al., 2020; Fan et al., 2019; Fiorucci & Distrutti, 2019; Nakhi et al., 2019). TCDCA also can promote apoptosis of mouse peritoneal macrophages (Fukumoto et al., 2002; Zan et al., 2020). Due to the drug resistance and adverse effects of currently used chemotherapies, TCM has recently received attention due to the relatively few side effects (Zhang et al., 2019).…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Baicalin shows characteristics associated with gastrointestinal hydrolysis, enterohepatic circulation, carrier transport, and complex metabolism, and baicalin can be converted into baicalein during the absorption process, the latter of which has antitumor, antibacterial, antioxidant, and some other pharmacological activities [10,11] . Ursodeoxycholic acid and chenodeoxycholic acid have effects on enterohepatic circulation, and each can be converted into the other by intestinal ora [8,12] . Chlorogenic acid has antipyretic, antiin ammatory, antibacterial, antiviral, and other pharmacological activities [13,14] .…”
Section: Introductionmentioning
confidence: 99%